1999
DOI: 10.1016/s0960-9822(99)80111-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory phosphorylation of the APC regulator Hct1 is controlled by the kinase Cdc28 and the phosphatase Cdc14

Abstract: We conclude that Hct1 phosphorylation is a key regulatory mechanism in the control of cyclin destruction. Phosphorylation of Hct1 provides a mechanism by which Cdc28 blocks its own inactivation during S phase and early mitosis. Following anaphase, dephosphorylation of Hct1 by Cdc14 may help initiate cyclin destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
382
0
11

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 396 publications
(403 citation statements)
references
References 43 publications
(77 reference statements)
10
382
0
11
Order By: Relevance
“…Clb2 was expressed from a 2μ P GAL1 -TAP plasmid, and Clb2-Cdk1 complexes were purified using a C-terminal TAP tag on Clb2 29. GST-Cdc14 was purified from bacteria 15 . Securin and Cdc20 were expressed in the TNT reticulocyte lysate coupled transcription/translation system (Promega) with a C-and N-terminal TEV-ZZ tag, respectively, purified rapidly on M-270 Epoxy dynabeads (Invitrogen) coupled to IgG, and eluted with TEV protease.…”
Section: Protein Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Clb2 was expressed from a 2μ P GAL1 -TAP plasmid, and Clb2-Cdk1 complexes were purified using a C-terminal TAP tag on Clb2 29. GST-Cdc14 was purified from bacteria 15 . Securin and Cdc20 were expressed in the TNT reticulocyte lysate coupled transcription/translation system (Promega) with a C-and N-terminal TEV-ZZ tag, respectively, purified rapidly on M-270 Epoxy dynabeads (Invitrogen) coupled to IgG, and eluted with TEV protease.…”
Section: Protein Purificationmentioning
confidence: 99%
“…Cdc14 is a phosphatase that removes phosphates from Cdk1 substrates during anaphase and late mitosis 4,[13][14][15][16] . We found that Cdc14 removed Cdk1-dependent phosphates from securin, as judged by the loss of a gel-mobility shift that results from phosphorylation ( Fig.…”
mentioning
confidence: 99%
“…Studies with purified APC from budding yeast and human cells demonstrate that both Cdc20 and Cdh1/ Hct1 activate the 'in vitro' ubiquitination of cyclin B (Kramer et al, 1998;Jaspersen et al, 1999). Moreover, the APC purified from Xenopus egg extracts in which Cdc20 function is blocked presents a clearly inhibited ubiquitination activity (Lorca et al, 1998).…”
Section: Apc Activators: Cdc20 Cdh1 and Ama1mentioning
confidence: 99%
“…The form of eqn (2) suggests that A is a phosphatase, removing from Cdh1 the inhibitory phosphate groups placed there by CycB/Cdk. Recent experimental evidence in budding yeast (Jasperson et al, 1999;Visintin et al, 1998) identi-"es A as the product of the CDC14 gene. At the metaphasePanaphase transition, Cdc14 phosphatase is activated indirectly by Cdc20/APC, which destroys an inhibitor of Cdc14.…”
Section: Activation Of Cdh1/apc At Anaphasementioning
confidence: 99%